Comparison of rituximab vs. cyclophosphamide in rheumatoid arthritis-associated interstitial lung disease and its correlation with spirometry - Mohammed Abdullah Saleem; Atiya Parveen; Fazeel Zubair Ahmed (The Journal of Association of Chest Physicians)
Introduction: Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is a significant health concern affecting a substantial population in India. This study outlines the limitations of current treatment options. Specifically, the toxicity of cyclophosphamide sets the stage for investigating the comparative effectiveness of rituximab in the context of RA-ILD. Methodology: This randomized, open-label study aimed to compare the efficacy and safety of rituximab and cyclophosphamide in treating severe or progressive RA-ILD. The inclusion and exclusion criteria, randomization process, and treatment protocols for each group are thoroughly described. The study’s ethical considerations, adherence to guidelines, and approval from the institutional ethics committee are highlighted. The comprehensive methodology encompasses patient recruitment, informed consent, treatment administration, and the rigorous assessment of clinical and spirometry parameters over a 48-week period. Results: The study enrolled 95 RA-ILD patients, randomly assigning them to rituximab and cyclophosphamide groups. The mean age, gender distribution, and baseline clinical parameters were comparable between the groups. Spirometry measurements, including forced vital capacity (FVC), were assessed at regular intervals up to 48 weeks. Results indicate that both rituximab and cyclophosphamide groups demonstrated improvement in FVC from baseline, with no statistically significant difference between the two groups at 24 and 48 weeks. Quality of life parameters, adverse effects, and other relevant clinical endpoints are thoroughly reported. Conclusion: Rituximab emerges as a comparable alternative to cyclophosphamide in increasing FVC and improving quality of life parameters in RA-ILD patients. Notably, rituximab demonstrated a superior safety profile with fewer adverse effects.